Occlusal traits of 4–5-year-old Estonians. Parents' perception of orthodontic treatment need and satisfaction with dental appearance - Sepp H.; Saag M.; Vinkka-Puhakka H.; Svedström-Oristo A.; Peltomäki T. (Wiley-Blackwell, 2022)
This study aims to evaluate the prevalence of occlusal traits and to assess parents'/caregivers' satisfaction with child's dental appearance and perception of orthodontic treatment need in 4–5‐year‐old Estonians. Clinical records and plaster casts of 390 children (190 girls and 200 boys, mean age 4.7 years, range 4 ̶ 5 years) were analyzed. Assessed occlusal traits included deciduous canine and second molar sagittal relationship, overjet, overbite, crowding, midline diastema, crossbite, and scissor bite. Parents'/caregivers' opinions regarding their child's teeth were determined with a questionnaire. The most prevalent occlusal traits were symmetrical sagittal relationship in deciduous canines (78.2%) and molars (75.1%), Class I sagittal relationship in deciduous canines (69.7%) and midline diastema (67.7%). Asymmetrical sagittal canine relationship was registered in 21.8% deciduous canines and in 24.9% second deciduous molars. Parents'/caregivers' perceived orthodontic treatment need was related to Class III sagittal relationship in canines, increased overjet and overbite, negative overbite, and crossbite. Prevalence of most occlusal traits in Estonian children were in line with those reported in neighboring countries. Parents/caregivers were well able to observe occlusal traits that deviated from acceptable occlusion.